Psychological Domain of Elderly Patients with Diabetic Retinopathy - O. L. Fabikantov; I. V. Lev; N. M. Agarkov; S. I. Nikolashin; A. A. Titov (Oftalʹmologiâ, 2023)
The continuing increase in the prevalence of diabetic retinopathy among various segments of the population and, especially in older age, combined with a change in the psychological state of such patients. However, the study of the holistic psychological (cognitivedepressive) domain in elderly patients with various stages of diabetic retinopathy, comparable in cardiovascular pathology, which is an independent risk factor for both diabetic retinopathy and cognitive impairment, depression not carried out.Purpose: to assess the psychological domain in patients 60–74 years old suffering from diabetic retinopathy standardized for concomitant cardiovascular pathology. In the Tambov branch of the Tambov branch of S.N. Fedorov NMRC “MNTK “Eye Microsurgery” in 2019–2020, cognitive impairment and depression were studied in 68 patients with non-proliferative, 62 patients with preproliferative and 70 elderly patients with proliferative stage on the Mini-Mental-State-Examination and Center for Epidemiologic Studies — Depression scale, respectively. The diagnosis of diabetic retinopathy established based on the results of a comprehensive ophthalmological examination. The control consisted of 59 patients with the absence of diabetic retinopathy. Patients with non-proliferative stage had mild (21.5 ± 0.3 points), and with preproliferative (17.9 ± 0.4 points) and proliferative stage (16.2 ± 0.3 points) moderate cognitive impairment. The association of cognitive impairment found with preproliferative and proliferative diabetic retinopathy. The level of depression in the non–proliferative stage was 22.4 ± 0.4 points, in the preproliferative stage — 24.8 ± 0.3 points and in the proliferative stage — 26.9 ± 0.5 points versus 19.2 ± 0.3 points in the control with a significant difference in all cases. The values of the relative risk of diabetic retinopathy stages were 1,337, 2,408 and 2,796, respectively. The revealed deterioration of the cognitive-depressive domain in elderly patients with diabetic retinopathy is important for improving compliance, the effectiveness of treatment of diabetic retinopathy and the psychological continuum.